Door-to-door livestock treatment in Boyolali Regency: Ruminant health evaluation strategy in Household Farms - Penny Humaidah Hamid; Dian Meididewi Nuraini; Wari Pawestri; Wahyu Kurniawan; Heri Kurnianto; Muhamad Cahyadi; Yuli Yanti; Joko Riyanto (Community Empowerment, 2023)
Ruminant husbandry is a fundamental economic aspect of Boyolali Regency. Animal health management is an important factor to guarantee the husbandry meets optimal production. The community service activity is aimed to contribute in controlling animal diseases at Boyolali. The service is carried out door to door accompanied by discussions with breeders and direct treatment of sick livestock. Interaction with breeders aims to provide practical education on the role of health in achieving efficient livestock production. The treatment provided included worming, vitamins, anti-ectoparasites, and pregnancy checks. The injection treatment was performed by veterinarians on 50 beef cattle, goats and sheep and proved to be effective in its implementation. This activity has been successful and all livestock can be diagnosed and treated according to the correct treatment mechanism.